Building cyber resilience before the next attack occurs : companies that are most successful in responding to cyberattacks leverage distributed leadership, crisis experience, and consistent communication - Hepfer, Manuel; Lawrence, Thomas B.; Meyrick, Julian; D'Urso, Pompeo (MIT Sloan Management Review, 2022)
Lessons and insights from past cyberattacks can help companies prepare and respond more successfully to future threats. The authors conducted in-depth interviews with senior leaders whose companies had previously endured serious cyberattacks to learn from their experiences. In this article, they describe three common mistakes people make that inhibit successful recovery from a cyberattack, as well as three elements at the heart of responding successfully to any attack.